The association of pericoronary adipose tissue attenuation with major adverse cardiac events (MACE) and atherosclerosis-relevant inflammatory mediators. (25th November 2020) - Goeller, M; Achenbach, S; Herrmann, N; Bittner, D; Ammon, F; Kilian, T; Smolka, S; Uehlein, S; Moshage, M; Raaz-Schrauder, D; Dey, D; Marwan, M
Abstract: Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) is a new imaging biomarker to detect coronary inflammation derived from routine coronary CT angiography (CTA). Purpose: We aimed to investigate a potential association between RCA PCAT attenuation and i) serum levels of atherosclerosis-relevant cytokines, ii) different grades of coronary calcification iii) future coronary revascularization within the same coronary artery and iV) MACE (defined by revascularization, myocardial infarction (MI) and/or cardiac death). Methods: In 293 stable individuals (59.0±9.8 years, 69% males) with intermediate likelihood for coronary artery disease (CAD) blood was drawn and subsequently analyzed for different atherosclerosis-relevant cytokines interleukin (IL)-2, IL- 4, IL-6, IL-7, IL-8, IL-10, IL-13, Il-15, IL-17, TNF-a, IP-10, CRP, MCP-1, MIP-1a, Eotaxin and GM-CSF, followed by coronary calcium scoring (CCS) in non-contrast CT followed by CTA. PCAT CT attenuation (HU) was measured around the RCA (10 to 50 mm from RCA ostium) and the proximal 40 mm of the left anterior descending artery (LAD) and the circumflex artery (LCX) using semi-automated software. Increased RCA PCAT attenuation was defined as PCAT attenuation above the highest quartile (>−73.5 HU). A long-term follow-up over 9.6 years was performed. Results: PCAT attenuation was similar in different grades of coronary calcification (CAC=0, -80.3 HU; CAC 1–99, −79.2 HU; CAC 100–400, −79.5 HU; CAC >400, −81.0 HU; p>0.05). Adipocytokine MCP-1 (r=0.23, p<0.01) and pro-inflammatory mediator IL-7 (r=0.12, p=0.04) correlated positively with RCA PCAT attenuation, whereas anti-inflammatory mediators Il-4, -10 and -13 correlated inversely (each r<−0.12, each p<0.05). In patients with increased RCA PCAT attenuation the serum levels of MCP-1 were increased (2.37 vs. 2.20, p<0.01), whereas anti-inflammatory mediators IL-4 and -13 were reduced (each p<0.05). 40 patients experienced MACE during follow-up. In multivariable Cox regression analysis, when adjusted by age, gender, baseline medications, obstructive coronary stenosis and CCS, the highest quartiles of PCAT attenuation are an independent predictor of MACE (HR 7.9, p=0.035). In patients with percutaneous coronary intervention (PCI) of the RCA during follow-up, RCA PCAT attenuation was increased at baseline CTA (−73.1 vs −80.2 HU, p=0.008). In patients with PCI of the LAD or LCX during follow-up, PCAT attenuation of LAD and LCX were not increased at baseline CTA (p>0.05). Conclusions: The information captured by PCAT attenuation is independent of coronary calcification and showed a trend towards a weak association with serum levels of atherosclerosis-relevant inflammatory biomarkers. Increased RCA PCAT attenuation is an independent predictor of MACE and could guide future prevention strategies in stable patients. Funding Acknowledgement: Type of funding source: None